2022
DOI: 10.1590/1981-6723.08122
|View full text |Cite
|
Sign up to set email alerts
|

Green banana and ora-pro-nóbis mixed flours: nutritional and technological characteristics

Abstract: The constant need for innovation in the food industries to meet the demands of consumers and the growing market for gluten-free and high-protein products have driven studies of mixed flour. In this study, 'BRS Platina' banana fruits were processed to obtain Whole Green Banana Flour (WGBF) and Green Banana Pulp Flour (GBPF) as well as leaves of Ora-pro-nóbis Flour (OPNF). Mixed flours were prepared by blending banana flours (WGBF or GBPF) with increasing levels of OPNF (from 5 to 25%). Flours were analyzed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
0
1
1
Order By: Relevance
“…The protein levels of OPN were 21.08% for the leaf and 9.56% for the stem (Table 1). These levels were higher than those found by Candido et al (2022) and Santos et al (2022), who reported protein contents of 17.7% and 18.7%, respectively. These same authors observed varying levels of protein in OPN flours that ranged between 28.4 and 28.99%.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…The protein levels of OPN were 21.08% for the leaf and 9.56% for the stem (Table 1). These levels were higher than those found by Candido et al (2022) and Santos et al (2022), who reported protein contents of 17.7% and 18.7%, respectively. These same authors observed varying levels of protein in OPN flours that ranged between 28.4 and 28.99%.…”
Section: Resultscontrasting
confidence: 78%
“…Table 1 shows results obtained in the analysis of OPN flour of the moisture and ash, however, it could be noted that there was no significant difference, which was also observed in other studies, when having insight into the contents of moisture varying from 7.38 to 12.46, and contents of ash varying from 12.57 to 25.69 (Almeida et al, 2014;Vargas et al, 2017;Candido et al, 2022;Santos et al 2022).…”
Section: Resultssupporting
confidence: 60%
“…L. pertenece a la familia-Musaceae y al orden-Zingiberales, y es originario del Sudeste de Asia desarrollándose en regiones tropicales y subtropicales en más de 150 países en el mundo (Galecio-Julca et al, 2020;Aguilar Anccota et al, 2021a;Ayres, 2022). Este fruto tiene un gran valor nutricional por su alto contenido de hidratos de carbono y sales minerales como Mg, Fe y Zn; así como, K, vitaminas A, B1, B2, B6 y C (Souza et al, 2017;Cândido et al, 2022). El 2021, se han reportado una producción mundial de 124,9 Millones de toneladas (Mt), siendo la India el principal productor con 32 (Mt), seguido de China (11,6 Mtn), Indonesia (8 Mtn), Brasil (6,7 Mtn), Ecuador (6,4 Mtn) (FAO, 2023).…”
Section: Introductionunclassified